Kontribusi Sektor Pertanian dan Pengaruhnya Terhadap Perekonomian Daerah Provinsi Jambi - Albetris Albetris (Universitas Batanghari, 2019)
The purpose of this research is to find out and analyze the large contribution of the agricultural sector to the economy of the regional province of Jambi and influence the agricultural sector against economic growth the province of Jambi. The object of the research is done in the agricultural sector, economic growth and GDP Jambi province. The data used in this research is the secondary data, this research are deskriptive quantitative, quantitative formulation can answer twist of the problem. The first results showed a contribution of the agricultural sector to the total GDP Jambi province for 13 years (in 2006 – the year 2018) that ranges from 25.12% to 27.44%, the greatest contribution took place in 2008, namely of 27.44% . Meanwhile, the contribution of the agricultural sector to the total GDP the lowest occurred in the year 2015, namely of 25.12%. the median contribution in sub sectors of the fishery towards the agricultural sector amounted to 26.19%. and the second results of the estimation of simple regression model shows a positive regression coefficient i.e. Y = 1.033 + 0340 X. This showing that the higher growth in the agricultural sector, it will spur economic growth in the province of Jambi 2005-2017 with the R-square of 99.10% with a confidence level significance alfa = 5%, that influence the agricultural sector very convincing. And 0.90% influenced by other factors.